Speciation of Candida and antifungal susceptibility from oral thrush cases in people living with HIV and its correlation with CD4 count and viral load in a tertiary care hospital: a cross-sectional study - Kumari, C. H. Aruna; Murthy, D. Satyanarayana; Kalyani, Siva; Grace, B. Nirmala; Rani, A. Durga; Kumar, P. V. Prasanna; Rukmini, S.; Rajesh (International Journal of Research in Medical Sciences, 2025)
Background: Oropharyngeal candidiasis (OPC) is the most common opportunistic infection observed in Human immunodeficiency virus (HIV) seropositive patients. It has been perceived that low CD4 counts and high plasma HIV RNA levels, both significantly correlate with oral candidiasis in HIV patients. Aim was to determine the antifungal susceptibility testing of the Candida isolates by disc diffusion method. Methods: The present study is a cross-sectional study that included 100 clinical samples processed for speciation of Candida isolates by using standard mycological techniques and antifungal susceptibility of the Candida isolates was done by using disc diffusion method and minimum inhibitory concentration (MIC’s) was done by ‘E’ strip test for fluconazole resistant isolates. CD4 count was estimated by using flow cytometry method and viral load was estimated by using real time PCR, Abbott M2000SP and correlated with oral thrush. Results: Out of 100 Candida isolates, C. albicans 84 (84%) was the predominant species followed by C. krusei 7 (7%), C. glabrata 6 (6%), C. tropicalis 3 (3%). Among the antifungals used in this study, the most sensitive agent was voriconazole 99 (94.4%) and the least was itraconazole 59 (19.6%). CD4 count was less than 200 cells/μl in 45 (45%). Viral load varied from 1,62409 to 58 copies/ml of blood in the patients with oral thrush with significant association. Conclusions: To conclude, though C. albicans was the common species, the emergence of non-albicans Candida species and the increasing rate of azole resistance, emphasizes the need for speciation and determination of susceptibility pattern to provide appropriate treatment for HIV patients with oral candidiasis.